Muon-spin-relaxation studies of magnetic order in heavily doped La2-xSrxNiO4+ delta. - Chow, K; Pattenden, P; Blundell, S; Hayes, W; Pratt, F; Jestädt, T; Green, M; Millburn, J; Rosseinsky, M; Hitti, B; Dunsiger, SR; Kiefl, R; et al. (1996)
We report muon-spin-relaxation measurements on a series of compounds with composition La2-xSrxNiO4+δ where the net hole concentration x+2δ is greater than 0.4. A magnetic transition is found in all the samples studied which occurs at a composition-dependent temperature TM. Below TM clear precession signals are observed in zero applied magnetic field, indicating the existence of at least short-range magnetic order on a time scale greater than 10-8 s. Above TM the correlation times decrease by several orders of magnitude. The measurements of TM as a function of the net hole concentration extend the determination of Néel temperatures by previous neutron diffraction measurements to higher doping levels.